(untitled) (La Aljaba, Segunda Época. Revista de Estudios de la Mujer, 2021)
The results of an investigation are presented that aimed to know the main psychosocial problems that occur in the state of Zacatecas, Mexico; The argument is that the escalation of violence that is being experienced is affecting the living conditions of the entire population. For this, the necessary information was collected to contextualize the phenomenon, achieving the identification of the main effects that have been occurring: depression, addictions and suicides, have the highest incidence. incidence. It is concluded that mental health and violence constitute a fragmented universe that negatively affects social behaviors. It also shows the lack of public policies and adequate budgets to generate specific care programs in the field of mental health, to reduce the harmful effects of violence.